Langerian Socio-Cognitive Approach to Learning in Universities: A Scoping Literature Review - Aleksandra Bordunos; Natalia Volkova; Maina Miletich (Вопросы образования)
Background:  Universities emphasize the importance of students’ mental health, engagement, and soft skills, such as critical thinking, communication, collaboration, creativity, and self-management.